TEACHING METHODOLOGY OF THE LLOYD’S MIRROR INTERFERENCE EXPERIMENT USING A He–Ne LASER - Akimova, Jumakhan Orazbayevna; Orazimbetova, Kalzhamal Oralbaevna (SCIENCE and SOCIETY, 2026)
This article provides an in-depth study of one of the important optical phenomena proving the wave nature of light, the Lloyd interference experiment, using a He-Ne laser. The article provides a detailed description of the theoretical foundations of the interference phenomenon, the physical essence of Lloyd’s experiment, the operating principle of the He-Ne laser, the experimental device and methodology, mathematical expressions, measurement results, and error analysis. The experimental results practically confirm the wave properties of light and demonstrate that laser beams are highly coherent.